To find the number that goes in place of ??? in your expression, we need to calculate the discriminant of the quadratic equation using the formula:
\[ D = b^2 - 4ac \]
In your equation \(2x^2 + 7x - 15 = 0\), the coefficients are:
- \(a = 2\)
- \(b = 7\)
- \(c = -15\)
Now, substituting these values into the formula:
\[ D = (7)^2 - 4(2)(-15) \]
Calculating each term:
- \( (7)^2 = 49 \)
- \( 4(2)(-15) = -120 \)
Now, substituting back into the discriminant formula:
\[ D = 49 - (-120) = 49 + 120 = 169 \]
So the expression under the square root in the quadratic formula becomes \( \sqrt{169} \).
Thus, the number that goes in place of ??? is 169.
Your equation is now:
\[ x = -7 \pm \sqrt{169}/4 \]